2012
DOI: 10.1007/s00122-012-1968-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis of elite European maize (Zea mays L.) inbred lines using AFLP, SSR, and SNP markers reveals ascertainment bias for a subset of SNPs

Abstract: Recent advances in high-throughput sequencing technologies have triggered a shift toward single-nucleotide polymorphism (SNP) markers. A systematic bias can be introduced if SNPs are ascertained in a small panel of genotypes and then used for characterizing a larger population (ascertainment bias). With the objective of evaluating a potential ascertainment bias of the Illumina MaizeSNP50 array with respect to elite European maize dent and flint inbred lines, we compared the genetic diversity among these materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
76
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 40 publications
16
76
1
Order By: Relevance
“…Principal component analysis (PCA) was performed separately on dent and flint DH lines. For the analyses of genotypic relatedness a subset of SNP markers known to generate ascertainment bias (Frascaroli et al 2013) was excluded.The similarity of linkage phases across two populations was calculated according to Technow et al (2012) for SNP pairs polymorphic in both populations under consideration. We calculated the fraction of SNP pairs with equal sign of the linkage disequilibrium D AB ¼ p AB 2 p A p B in both populations, where p AB denotes the haplotype frequency of AB, p A the frequency of allele A at one marker locus, and p B the frequency of allele B at the other locus.…”
mentioning
confidence: 99%
“…Principal component analysis (PCA) was performed separately on dent and flint DH lines. For the analyses of genotypic relatedness a subset of SNP markers known to generate ascertainment bias (Frascaroli et al 2013) was excluded.The similarity of linkage phases across two populations was calculated according to Technow et al (2012) for SNP pairs polymorphic in both populations under consideration. We calculated the fraction of SNP pairs with equal sign of the linkage disequilibrium D AB ¼ p AB 2 p A p B in both populations, where p AB denotes the haplotype frequency of AB, p A the frequency of allele A at one marker locus, and p B the frequency of allele B at the other locus.…”
mentioning
confidence: 99%
“…The segregation test was carried out in order to verify whether the simulation process established a population with genetic characteristics of an F 2 population, as proposed by Falconer and Mackay (1996). It was observed that the allelic and genotypic frequencies were close to the expected value for an F 2 population, for all the markers that control the trait (QTL -Table 1) and the other simulated markers ( Table S1).…”
Section: Marker Segregation Testmentioning
confidence: 99%
“…The great importance of recovering all the information from an F 2 population using the simulation process is that the genetic variance, environmental variance, and heritability are easy to estimate in this type of population. According to Falconer and Mackay (1996), genetic variance in F 2 population is estimated as follows: in which d value was simulated as 0 for all loci, and thus the genetic variance is equal to the additive variance. This is easily calculated, since 2 α is the variance of the markers calculated using the RR-BLUP method.…”
Section: Marker Segregation Testmentioning
confidence: 99%
See 2 more Smart Citations